Sanctuary cities and urban struggles : rescaling migration, citizenship, and rights - Darling, Jonathan; Bauder, Harald, 1969- (Manchester University Press, 2019)
This book brings together an interdisciplinary team of scholars to explore how urban social movements, localised practices of rights claiming, and diverse articulations of sanctuary are reshaping the governance of migration.